Experimental Study on Performance of Asphalt Mixture Designed by Different Method. (2016) - Han, Dingding; Wei, Lianyu; Zhang, Jinxi
Abstract: In order to explore the Marshall, Superpave and GTM methods, the similarities and differences of the three design methods are detail studied. Experimental study on performance of asphalt mixture AC-13、AC-20 and AC-25 designed by different method were executed in this paper. Test results show that, GTM method gives lower void and lower bitumen aggregate ratio than other two methods, it have very better water stability and high-temperature stability. The DS value is 3256 / mm by GTM design method, is 1.91 times of the Marshall and 1.33 times of the Superpave. Superpave method gives lower bitumen aggregate ratio than Marshall method. The asphalt mixture designed by Superpave method has longer fatigue life than the mixture designed by other two methods. The volume parameters of asphalt mixture designed by Marshall can conform specification very well, but the performance of asphalt mixture seems to be worse than other two methods.